Remote effects of extracorporeal shock wave therapy on cutaneous microcirculation. Issue 4 (November 2015) - Kisch, Tobias; Sorg, Heiko; Forstmeier, Vinzent; Knobloch, Karsten; Liodaki, Eirini; Stang, Felix; Mailänder, Peter; Krämer, Robert
Abstract: Background: Extracorporeal shock wave treatment (ESWT) has proven its clinical benefits in different fields of medicine. Tissue regeneration and healing is improved after shock wave treatment. Even in the case of burn wounds angiogenesis and re-epithelialization is accelerated, but ESWT in extensive burn wounds is impracticable. Hypothesis: High energy ESWT influences cutaneous microcirculation at body regions remote from application site. Methods: Eighteen Sprague Dawley rats were randomly assigned to two groups and received either high energy ESWT (Group A: total 1000 impulses, 10 J) or placebo shock wave treatment (Group B: 0 impulses, 0 J), applied to the dorsal lower leg of the hind limb. Ten minutes later microcirculatory effects were assessed at the contralateral lower leg of the hind limb (remote body region) by combined Laser-Doppler-Imaging and Photospectrometry. Results: In Group A cutaneous capillary blood velocity was significantly increased by 152.8% vs. placebo ESWT at the remote body location (p = 0.01). Postcapillary venous filling pressure remained statistically unchanged (p > 0.05), while cutaneous tissue oxygen saturation increased by 12.7% in Group A (p = 0.220). Conclusion: High energy ESWT affects cutaneous hemodynamics in body regions remote from application site in a standard rat model. The results of this preliminary study indicate that ESWT might be beneficial even in disseminated and extensive burn wounds by remote shock wave effects and should therefore be subject to further scientific evaluation. Highlights: Extracorporeal shock wave treatment (ESWT) accelerates re-epithelialization in wounds. Here, cutaneous blood velocity was significantly increased by 152.8% at a remote body location. Postcapillary venous filling pressure remained statistically unchanged at the remote location. Cutaneous tissue oxygen saturation increased by 12.7% at the remote location. ESWT might be beneficial in disseminated and extensive wounds by remote effects.